Blended tube feeding prevalence, efficacy, and safety: What does the literature say?. Issue 3 (March 2018) - Carter, Holly; Johnson, Kelly; Johnson, Teresa W.; Spurlock, Amy
Abstract : Background and purpose: For most of human history, physicians used blended whole foods for patients who are unable to eat by mouth. However, by the 1960s and 1970s, advances in enteral nutrition resulted in the gradual displacement of blenderized tube feedings (BTFs) with commercial formulas. There are advantages and disadvantages to commercial formulas and BTFs. The purpose of this article was to review the literature for the incidence of blended tube feeding use and its safety, efficacy, and implications for clinical practice. Methods: A search of the scientific literature in PubMed, CINAHL, Cochrane, ProQuest, and Ovid was conducted using the keywords "blenderized tube feeding" and "blended tube feeding." Articles were divided into two categories: 1) frequency of use and experiences of BTF in patients or caregivers and health care providers and 2) safety/efficacy studies. Conclusions: The literature review shows a rising interest in BTF, with more research on efficacy indicated. Implications for practice: The use of BTF is primarily patient or caregiver driven. Blenderized tube feeding requires oversight by health care providers just as commercial formulas. Health care providers should be aware of the use of BTF and the effect it can have on different patient populations regarding content, cost, safety, and efficacy in the clinical and home settings.